Facts and Fictions: Focusing on TripAdvisor Reviews of Mount Tangkuban Parahu - Aditya Rizki Rinaldi (Politeknik Negeri Bandung, 2023)
Folklore as a form of intangible cultural heritage can be used as a strong cultural capital for tourism development. The existence of the legend of Sangkuriang, which is thick among the Sundanese community, and other aspects such as geological and volcanological aspects become tourism strengths of Mount Tangkuban Parahu. Using content analysis on traveler reviews on TripAdvisor pages, this article explores how